Analisis Lingkungan Internal dan Eksternal Sub Terminal Agribisnis Komoditi Mentimun di Kelurahan Koto Baru Payo Basuang Kecamatan Payakumbuh Timur - Ziret Nengsih; Husnarti Husnarti; Revi Ernanda (Mahesa Research Institute, 2024)
The mechanism for the agribusiness sub terminal is to collect agricultural production from the agribusiness sub terminal and partner farmers and then from traders who make pre-orders by telephone through the agribusiness sub terminal administrator. The highest bid will receive agricultural products. According to Tanjung (2018), STA is marketing infrastructure located in production centers as a place for buying and selling agricultural products, related to physical and non-physical trade, so that the focus of STA is the marketing space carried out by central producers. This research aims to first find out the internal and external environmental factors that influence STA Koba Jaya in Koto Baru Payo Basuang Village, secondly to find out the strategy for developing STA Koba Jaya in Koto Baru Payo Basuang Village. This research was carried out from July to September 2023. The research method used was descriptive qualitative. The results of this research show that the internal factors that influence the STA of cucumber commodities are: product quality, price information, product non-durability, financial condition and lack of operational vehicles. External factors that influence STA Koba Jaya cucumber commodities: market share, number of collecting traders, product price fluctuations, government support and promotions